Modernist novel : a critical introduction - Kern, Stephen (Cambridge University Press, 2011)
"Leading scholar Stephen Kern offers a probing analysis of the modernist novel, encompassing American, British and European works. Organized thematically, the book offers a comprehensive analysis of the stunningly original formal innovations in novels by Conrad, Joyce, Woolf, Proust, Gide, Faulkner, Dos Passos, Kafka, Musil and others. Kern contextualizes and explains how formal innovations captured the dynamic history of the period, reconstructed as ten master narratives. He also draws briefly on poetry and painting of the first half of the twentieth century. The Modernist Novel is set to become a fundamental source for discussions of the genre and a useful introduction to the subject for students and scholars of modernism and twentieth-century literature"--